2009
DOI: 10.1177/1753193409103728
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular distal ulnar fractures associated with distal radial fractures in older adults: early experience in fixation of the radius and leaving the ulna unfixed

Abstract: There is no clear consensus about the best management of intra-articular distal ulnar fractures associated with distal radial fractures in older adults. We describe a treatment wherein the distal radial fractures were securely fixed with a palmar plate, leaving the associated ulnar fractures unfixed. The wrists of 14 patients with a mean age of 74 years were reviewed at an average of 18 months after surgery. The results were excellent in 11 cases and good in three, according to the modified Gartland and Werley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“…The rate of ulnar styloid fracture in our study was 58%. Our results were consistent with previous reports that ulnar styloid fractures are usually present in 50% to 65% of the DRF [17,19,21,25,31]. The incidence of the TFCC tear complicated to the DRF was reported to vary widely from 9% to 84% [32-36].…”
Section: Discussionsupporting
confidence: 93%
“…The rate of ulnar styloid fracture in our study was 58%. Our results were consistent with previous reports that ulnar styloid fractures are usually present in 50% to 65% of the DRF [17,19,21,25,31]. The incidence of the TFCC tear complicated to the DRF was reported to vary widely from 9% to 84% [32-36].…”
Section: Discussionsupporting
confidence: 93%
“…Four small case series described unplanned surgery in 0 to 33% of patients. 1,[8][9][10] A recent review concluded that there is no consensus on operative versus nonoperative management of ulnar metaphyseal fractures. 11 One case series described one unplanned surgery of the ulnar neck after an open fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Pour les fractures du col ou de la tête ulnaire, métaphyso-épiphysaires, plusieurs attitudes ont été décrites, de la fixation (parfois difficile en cas d'os très porotique), à la résection d'emblée. Récemment, Namba et al ont montré que l'abstention sur l'ulna associée à une synthèse du radius était suivie de bons résultats fonctionnels dans une population âgée [71]. En cas de luxation de l'articulation RUD, la lésion du complexe triangulaire est constante associée à des lésions de la membrane interosseuse à sa partie distale : la réduction et l'arthrorise temporaire sont nécessaires ; en revanche, une lésion du complexe triangulaire n'est pas synonyme d'instabilité constante.…”
Section: Le Problème De L'ulnaunclassified